2019
DOI: 10.1093/neuonc/noz185
|View full text |Cite
|
Sign up to set email alerts
|

Window-of-opportunity clinical trial of pembrolizumab in patients with recurrent glioblastoma reveals predominance of immune-suppressive macrophages

Abstract: Background We sought to ascertain the immune effector function of pembrolizumab within the glioblastoma (GBM) microenvironment during the therapeutic window. Methods In an open-label, single-center, single-arm phase II “window-of-opportunity” trial in 15 patients with recurrent (operable) GBM receiving up to 2 pembrolizumab doses before surgery and every 3 weeks afterward until disease progression or unacceptable toxicities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 38 publications
1
93
0
1
Order By: Relevance
“…The recent JAVELIN Ovarian 100 trial, which evaluated a αPD-1 antibody (avelumab) in combination with and/or following platinum-based chemotherapy in 998 previously untreated patients, found a poor overall response. Similar outcomes have been also reported in gastric, and brain malignancies (24,25,34,35). The immunosuppressive TME in these cancer types is particularly challenging to overcome.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The recent JAVELIN Ovarian 100 trial, which evaluated a αPD-1 antibody (avelumab) in combination with and/or following platinum-based chemotherapy in 998 previously untreated patients, found a poor overall response. Similar outcomes have been also reported in gastric, and brain malignancies (24,25,34,35). The immunosuppressive TME in these cancer types is particularly challenging to overcome.…”
Section: Discussionsupporting
confidence: 68%
“…To date, the single agent activities of anti-PD-1 and anti-PD-L1 inhibitors in some cancers have being disappointing (24,26). The recent JAVELIN Ovarian 100 trial, which evaluated a αPD-1 antibody (avelumab) in combination with and/or following platinum-based chemotherapy in 998 previously untreated patients, found a poor overall response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely studied immune checkpoint in the eld of cancer is PD-L1/PD-1. But study found that the therapeutic effect was not satisfactory and there were differences in therapeutic effect [48]. Current clinical studies of non-small cell lung cancer have assumed that people with PD-L1 high levels of expression bene t more from the use of immune checkpoint inhibitors than patients with low or no PD-L1 expression [49].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that patients treated with Pembrolizumab did not experience improved survival with treatment [75]. In view of the failure of ICIs in the clinic, a Phase II window-of-opportunity trial (NCT02337686) was conducted to assess the immune effector cells upon treatment with an ICI [76]. This study examined the relative numbers of CD3 + lymphocytes and CD68 + monocytes in tumors in order to determine the composition of the immune infiltrate in recurrent GBM tumors after treatment with Pembrolizumab.…”
Section: Clinical Experience With Using Icis To Treat Gbmmentioning
confidence: 99%